CD133 in breast cancer cells and in breast cancer stem cells as another target for immunotherapy - Tume, L (2016)
Breast cancer consists of a heterogeneous group of tumors with different features, biology and treatments. Cancer stem cells (CSCs) have been associated with an aggressive cellular behavior, resistance to chemotherapy and radiotherapy in many types of neoplasms, and a strong correlation between prominin-1 (CD133) expression in cancer stem cells from different types of cancer exist. A discussion is presented on recent immunotherapeutic strategies that target CD133 in breast CSCs. Furthermore, it is suggested that immunotherapy targeting CD133 breast CSCs and/or in combination with other current treatments result in a better outcome. © 2016 Sociedad Mexicana de Oncología.